Advancing maternal and perinatal health in low- and middle-income countries: A multi-country review of policies and programmes - Syed, Uzma; Kinney, Mary V.; Pestvenidze, Ekaterine; Vandy, Alren O.; Slowing, Karin; Kayita, Janet; Lewis, Alyona F.; Kenneh, Sartie; Moses, Francis L.; Aabroo, Atiya; Thom, Ellen; Uzma, Qudsia; et al. (Frontiers in Global Women's Health, 2022)
The Sustainable Development Goals prioritize maternal mortality reduction, with a global average target of < 70 per 100,000 live births by 2030. Current pace of reduction is far short of what is needed to achieve the global target. It is estimated that globally there are 300,000 maternal deaths, 2.4 million newborn deaths and 2 million stillbirths annually. Majority of these deaths occur in low-and-middle-income countries. Global initiatives like, Ending Preventable Maternal Mortality (EPMM) and Every Newborn Action Plan (ENAP), have outlined the broad strategies for maternal and newborn health programmes. A set of coverage targets and ten milestones were launched to support low-and-middle-income countries in accelerating progress in improving maternal, perinatal and newborn health and wellbeing. WHO, UNICEF and UNFPA, undertook a scoping review to understand how country strategies evolved in different contexts over the past two decades to improve maternal survival and wellbeing, and how countries in similar settings could accelerate progress considering the changing epidemiology and demography. Case studies were conducted to inform countries in similar settings and various global initiatives. Six countries were selected based on standard criteria—Cambodia, Democratic Republic of the Congo, Georgia, Guatemala, Pakistan and Sierra Leone representing different stages of the obstetric transition. A conceptual framework, encapsulating the interrelated factors impacting maternal health outcomes, was used to organize data collection and analysis. While all six countries made remarkable progress in improving maternal and perinatal health, the pace of progress and the factors influencing the successes and challenges varied across the countries. The context, opportunities and challenges varied from country to country. Two strategic directions were identified for next steps including the need to implement and evaluate innovative service delivery models using an updated obstetric transition as an organizing framework and expanding our vision to address equity and well-being.